Environmental detection of Fasciola hepatica by loop-mediated isothermal amplification - Lily Tran; Hayley Toet; Travis Beddoe (PeerJ, 2022)
Fasciola hepatica, commonly referred to as liver flukes, is a substantial zoonotic parasitic disease of humans and livestock globally. While infection is readily controlled by anthelmintics, namely triclabendazole, the heavy reliance on triclabendazole has resulted in drug resistance appearing worldwide. Due to drug resistance, it is imperative to adopt an integrated parasite management program to preserve the efficacy of currently available anthelmintics. A integrated liver fluke management plan would benefit from a simple rapid, field-deployable diagnostic for detection of F. hepatica in environment and the host. Therefore, a rapid DNA test using loop-mediated isothermal amplification was developed and optimised for the detection of F. hepatica from faecal and water samples to enable the detection of parasites both within the host and from the environment. The assay presented here is fast, with amplification in ≤20 min, and highly sensitive, with a detection limit of 5 × 10−4 ng/µL. The workflow presented here provides a time to result of ≤60 min without requiring a commercial kit for the extraction of DNA from faecal and water samples, and pending further validation from field-samples, could potentially be used to enable real-time decision making to mitigate parasite prevalence on a farming property and with no requirement for sample transportation.